Effectiveness of hepatitis B rapid tests toward linkage-to-care: results of a randomized, multicenter study. Issue 6 (June 2016) - Bottero, Julie; Boyd, Anders; Gozlan, Joël; Carrat, Fabrice; Lemoine, Maud; Rougier, Hayette; Varsat, Brigitte; Boo, Nicolas; Charlois-Ou, Cécile; Collignon, Anne; Cha, Olivier; Campa, Pauline; et al.
Abstract : Objectives: Worldwide, many infected individuals are unaware of their hepatitis B virus (HBV) status. We evaluated the effectiveness of HBV rapid testing in promoting linkage-to-care. Methods: In 2012, volunteers were recruited from five Parisian centers. Participants were randomized 1 : 1 to receive standard serology (S) or rapid testing (VIKIA-HBsAg/Quick Profile anti-HBsAb) with confirmatory serology (R+S). The primary endpoint was percentage of individuals with appropriate linkage-to-care (nonimmunized individuals starting vaccination or HBsAg-positive individuals receiving medical evaluation). The secondary outcomes were percentage receiving HBV-test results and performance of HBV rapid tests. Results: In total, 995 individuals were screened. Among the HBV-infection groups included in the primary endpoint ( n =409), 20 (4.9%) received appropriate linkage-to-care, with no difference between S and R+S groups (5.7 vs. 4.1%, P =0.5). Two of eight HBsAg-positive participants had a medical visit (1/6 and 1/2 in the S and R+S groups, respectively) and 18/401 (4.5%) nonimmunized participants initiated HBV-vaccination (11/205 and 7/196). Factors that tended to be associated with linkage-to-care were female sex, birth country of high HBV prevalence, and extended medical stay. Test results were not obtained in 4.7% of participants, which was significantly higher in the S arm ( P =0.02). Both sensitivity and specificity were 100% for the VIKIA-HBsAg rapid test and 94.4 and 80.8%, respectively, for the anti-HBsAb Quick Profile rapid test. Conclusion: Despite a higher proportion of participants obtaining their results in the R+S arm and better performance of anti-HBsAb rapid tests than described previously, we found no evidence that HBV screening based initially on rapid tests leads to increased HBV-vaccination rates or medical evaluation. This strategy should be evaluated in more hard-to-reach populations.